1996
DOI: 10.1159/000244325
|View full text |Cite
|
Sign up to set email alerts
|

Possible Effects of Placental Leucine Aminopeptidase on the Regulation of Brain-Gut Hormones in the Fetoplacental Unit

Abstract: The hydrolysis of somatostatin by human placental subcellular fractions and pregnancy sera was studied in the presence of selective inhibitors and the antibody against pregnancy serum oxytocinase (placental leucine aminopeptidase; EC3.4.11.3) by measuring the released amino acids by high-performance liquid chromatography. We also studied the degradation of other brain-gut hormones, such as glucagon, growth hormone, growth hormone releasing factor, and insulin, in the human placenta and found that the human pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…IRAP/P-LAP cleaves vasopressin, oxytocin, lysbradykinin, angiotensins III and IV, and the neuropeptides met-enkephalin and dynorphin A(1-8) in vitro (36,62,63). Other peptide hormones, among these insulin, have been tested for cleavage by IRAP/P-LAP and found to be unlikely substrates for IRAP/P-LAP (63,64). The cleavage of the N-terminal amino acid from each angiotensin converts it from one active form to another active form (65).…”
Section: Peptide Hormones Cleaved By Irap/p-lapmentioning
confidence: 99%
“…IRAP/P-LAP cleaves vasopressin, oxytocin, lysbradykinin, angiotensins III and IV, and the neuropeptides met-enkephalin and dynorphin A(1-8) in vitro (36,62,63). Other peptide hormones, among these insulin, have been tested for cleavage by IRAP/P-LAP and found to be unlikely substrates for IRAP/P-LAP (63,64). The cleavage of the N-terminal amino acid from each angiotensin converts it from one active form to another active form (65).…”
Section: Peptide Hormones Cleaved By Irap/p-lapmentioning
confidence: 99%
“…Because the enzyme cleaves oxytocin and vasopressin between the N-terminal halfcystine residue and the penultimate tyrosine, it is also referred to as cystine or cystyl-aminopeptidase (CAP; EC 3.4.11.3) (Tuppy, 1968;Roy and Karim, 1983). In addition, it was reported that human placental leucine aminopeptidase (P-LAP) is identical to CAP and degrades angiotensin III (Tsujimoto et al, 1992) and somatostatin (Mizutani et al, 1996) as well as oxytocin and vasopressin. Therefore, this enzyme is an αaminoacyl-peptide hydrolase with a broad specificity, hydrolyzing peptide bonds with aromatic neutral and basic N-terminal amino acid residues in the peptides (Ryden, 1966;Sakura et al, 1981;Roy et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…LF-A1, LF-B1, LF-B2 and LF-C (Olsen et al 1991(Olsen et al , 1995Shapiro et al 1991). An enhancer region of about 300 bp that is localized 2.7 kb upstream of the epithelial promoter seems to enhance the activity ofboth promoters (Olsen et al 1997) APN is supposed to be involved in the degradation of neuropeptides (Ahmad et al 1992;Furuhashi et al 1988;Giros et al 1986;Miller et al 1994aMiller et al , 1994bMizutani et al 1993;Shibanoki et al 1991;Shimamura et al 1988Shimamura et al , 1991Ward et al 1990), cytokines and immunomodulatory peptides (Hoffmann et al 1993;Kanayama et al 1995;Mathe 1987), and angiotensins (Chansel et al 1998;Palmieri et al 1989;Palmieri et al 1985). Furthermore, APN may contribute in extracellular matrix degradation (Fujii et al 1995;Saiki et al 1993) and antigen processing (Hansen et al 1993;Larsen et al 1996).…”
Section: Characteristics and Functionsmentioning
confidence: 99%